Munasabah dalam Tafsir Al-Qur’an: Pilar Keterpaduan Teks Wahyu Menuju Pemahaman Kontekstual - Ariza, Fauziah Nur; Kurniawan, Hendra (Medan Resource Center, 2024)
This study aims to analyze the pattern of munasabah or the correlation between verses and chapters in the Qur’an, encompassing causal relationships, comparisons, contrasts, and thematic repetitions. Munasabah plays a crucial role in clarifying the logical and aesthetic connections between verses, helping readers gain a deeper understanding of the Qur’an. This study employs a qualitative, literature-based approach, referring to the theories of scholars such as As-Suyuthi, Nasr Abu Zaid, and Quraish Shihab. The findings reveal causal relationships in Surah Al-Baqarah verses 152 and 186, which emphasize the importance of remembering and being grateful to Allah as a consequence of His guidance. Comparative patterns are observed in Surah Al-Anfal verse 28 and Surah Al-Hadid verses 22-23, highlighting the contrast between worldly and eternal life. Contrasting patterns appear in Surah Al-Baqarah verses 258-259, illustrating the differences between believers and disbelievers. Meanwhile, thematic repetition is evident in Surah Ar-Rahman through the recurring phrase,